2016
DOI: 10.1002/app.43717
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced chloroprene rubber by in situ generated silica particles: Evidence of bound rubber on the silica surface

Abstract: Nano silica is generated in situ inside the uncrosslinked chloroprene rubber (CR) by the sol-gel reaction of tetraethoxysilane (TEOS). This results in appreciable improvement in mechanical properties of the CR composites at relatively low filler content. Furthermore, exploitation of reactive organosilanes, g-aminopropyltrimethoxysilane (g-APS) in particular, in the silica synthesis process facilitates growing of spherical silica particles with a size distribution in the range of 20-50 nm. The silica particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…It is demonstrated that the formation of bound rubber is caused by the significant interfacial interactions between the rubber and filler . Thus the bound rubber content can be used to measure the strength of the interaction between the filler and rubber .…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that the formation of bound rubber is caused by the significant interfacial interactions between the rubber and filler . Thus the bound rubber content can be used to measure the strength of the interaction between the filler and rubber .…”
Section: Resultsmentioning
confidence: 99%
“…Improving the performance of polymer products by incorporating fillers has long been an important industrial activity, and traditionally this has been achieved by using materials such as carbon black, carbon nanofibers, clay, talc, and silica . Among them, the reinforcement of elastomers by silica has been studied in numerous studies .…”
Section: Introductionmentioning
confidence: 99%
“…Matrix‐free nanocomposites have a dispersion advantage compared to traditional composites that are prepared by blending rubber directly with nanoparticles. Traditional composite synthesis procedures require the mixing of particles with the polymer matrix, which often introduces agglomeration of particles particularly with high nanoparticle loadings due to undesirable interface compatibility . The grafted nanoparticles are separated from each other by the polymer brushes that were polymerized on the surface of these particles.…”
Section: Resultsmentioning
confidence: 99%